(untitled) - Yamaguchi, Minoru (Tokyo, 1969)
This book consists of the following many parts: Zen, its historical background and world vision, bergson and his philosophy, personal experiences of Zen masters, thinking methods of zen and bergson, nature of intuition of Zen and bergson, synthetical aspects of continuum and intuition.
Keywords: Zen Buddhism,Philosophy, comparative